2022
DOI: 10.3892/mmr.2022.12642
|View full text |Cite
|
Sign up to set email alerts
|

Icariin attenuates thioacetamide‑induced bone loss via the RANKL‑p38/ERK‑NFAT signaling pathway

Abstract: There is an increasing incidence of destructive bone disease caused by osteoclast proliferation. This is characterized by reduced bone mass and imbalance of bone homeostasis. Icariin (ICA), a flavonoid compound isolated from Epimedium , has anti-osteoporosis activity and inhibits the formation of osteoclasts and bone resorption. The purpose of the present study was to investigate the protective effect of ICA on osteoclastic differentiation induced by thioacetamide (TAA) and its possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Icariin is a natural flavonoid found in several plant species belonging to the Epimedium genus. Icariin has biological roles and pharmacological activities, including antiaging, antiosteoporosis, antioxidative, antiatherosclerotic, and anticancer activities [ 161 , 162 , 163 , 164 , 165 ]. Additionally, icariin exerts anti-inflammatory effects by inhibiting the priming step and canonical inflammasomes in inflammatory responses and diseases [ 166 , 167 , 168 , 169 , 170 , 171 ].…”
Section: Flavonoid-mediated Anti-inflammatory Roles By Targeting Casp...mentioning
confidence: 99%
“…Icariin is a natural flavonoid found in several plant species belonging to the Epimedium genus. Icariin has biological roles and pharmacological activities, including antiaging, antiosteoporosis, antioxidative, antiatherosclerotic, and anticancer activities [ 161 , 162 , 163 , 164 , 165 ]. Additionally, icariin exerts anti-inflammatory effects by inhibiting the priming step and canonical inflammasomes in inflammatory responses and diseases [ 166 , 167 , 168 , 169 , 170 , 171 ].…”
Section: Flavonoid-mediated Anti-inflammatory Roles By Targeting Casp...mentioning
confidence: 99%
“…A recent study suggested that ICA exerted an estrogenic effect in bones and activated the phosphorylation of estrogen receptor α (ERα) in osteoblasts [12]. In addition, ICA may indirectly regulate bone cell differentiation through the RANK/RANKL signaling [13]. How ERα and the RANK signaling are involved in ICA-mediated osteoclast differentiation warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Nakano [ 20 ] also found decreased bone volume and increased bone resorption in TAA-induced cirrhotic rats. Our previous research found that intraperitoneal injection of TAA can induce cortical bone damage and increase trabecular separation in SD rats [ 21 23 ]. In addition, TAA, which has the same effect as the classical osteoclast inducers RANKL and M-CSF, can induce BMMs differentiate into osteoclasts in vitro by inducing phosphorylation of PI3K, AKT, p38 and JNK and upregulating the expression of osteoclast specific proteins TRAP and cathepsin K [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TAA, which has the same effect as the classical osteoclast inducers RANKL and M-CSF, can induce BMMs differentiate into osteoclasts in vitro by inducing phosphorylation of PI3K, AKT, p38 and JNK and upregulating the expression of osteoclast specific proteins TRAP and cathepsin K [ 23 ]. TAA can also enhance the activity of osteoclasts and promote bone resorption [ 21 ]. However, the effect of TAA on osteogenic differentiation is still unclear.…”
Section: Introductionmentioning
confidence: 99%